Novels and other writings - Wharton, Edith (The Library of America, 1990)
Collected here in one volume are six works that represent nearly a quarter century in the productive life of one of the most accomplished and admired of American writers. They explore the private worlds of our "Gilded Age." A once free-spirited American woman in Paris tries to extricate herself from her marriage to a French aristocrat in "Madame de Treymes." A divorced mother finds herself in a strange romantic triangle in "The Mother's Recompense